Implementation of the Virtual Education Model in Solar System Learning for Class VII MTS Negeri 1 Sidenreng Rappang - Budiman Salam; Wahyu Hidayat; Rustan Effendy (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study was to describe the Virtual Education model and analyze the understanding of the concept of the Solar System using Virtual Education in class VII students of MTs Negeri 1 Sidenreng Rappang. This research uses classroom action research (CAR). Data was collected using observation, test, and documentation. The score data of the Solar System material test results are presented descriptively, namely frequency, percentage, graph, mean, and standard deviation. Data of observations used qualitative analysis techniques, namely by summarizing and describing the results of research through observational observations. The results of the study indicate that the application of the virtual education model makes students enthusiastic where students enjoy and are happy in the learning process. Meanwhile, the percentage of students whose scores were above the KKM in the first cycle reached 78.60%, so they still could not achieve the research success criteria. In cycle II, the steps for implementing the Virtual Education model were done by giving motivation, showing videos using LCD and virtual reality, and providing opportunities for group presentations on the results of the pictures in front of the class. For the percentage of students' scores above the KKM in the second cycle, it increased to 92.85%.